The Influence of Instructional Media on Students’ Success in Tanzania Secondary Schools - L. Nzilano, Eleuter; Machumu, Haruni (Indonesian Journal of Instructional Media and Model, 2025)
This study seeks to unpack the influence of instructional media on students` success in secondary schools located in the rural district of Southern Tanzania. The study used a quantitative research approach with randomization and simple sampling procedures to select schools and respondents. The study deployed a physically administered survey and collected data from 1,246 secondary school students. The study first deployed the exploratory and confirmatory factor analyses to establish the constructs' validity and reliability. It further deployed the stepwise multiple ordinary least squares regression analyses to test the selected hypotheses. The findings reveal that socioeconomic factors and instructors` and learners` characteristics positively influence instructional media usage in secondary schools. Further, the findings indicate a positive relationship between instructional media usage and students' success. Perceived ease of use and student success were also found to have a positive moderating role in the relationship between instructional media usage and students' success. The findings imply that using appropriate and modern instructional media tools during teaching significantly impacts students` understanding and success. Irrefutably, proper use of instructional media appears to influence student success, and student success can be achieved when instructional media are correctly determined and selected during their use.